Hubungan Indeks Massa Tubuh (IMT) dengan Angka Kejadian Osteoartritis di Rumah Sakit Ibnu Sina - Muhajir, Agung; Sam, A. Dhedie Prasatia; Abdullah, Rezky Putri Indarwati; N, Hermiaty; Sommeng, Faisal (Indonesian Journal of Health, 2022)
Osteoarthritis is a degenerative and inflammatory joint disease that causes pathological changes throughout the joint structure. This disease can be triggered by various risk factors, both systemic and local. One significant risk factor is excess body weight, which increases the likelihood of osteoarthritis, especially in weight-bearing joints such as the knees, regardless of gender. This study aims to examine the relationship between body mass index (BMI) and the prevalence of osteoarthritis at Ibnu Sina Hospital in Makassar. Using an observational analytic method with a retrospective design, this study investigates the correlation between BMI and the incidence of osteoarthritis. Data collection was conducted through total sampling technique, and statistical analysis was performed using Kendall's tau test. The results showed that out of a total of 100 patients, 50% were diagnosed with osteoarthritis and 50% were not. The BMI distribution of patients was as follows: 8% underweight, 24% normal, 26% overweight, 22% class 1 obesity, and 20% class 2 obesity. Statistical analysis using Kendall's tau test with a significance level of α = 5% (0.05) yielded a p-value of 0.000. Since the p-value (0.000) is less than α (0.05), H0 is rejected. This result indicates a significant relationship between body mass index (BMI) and the incidence of osteoarthritis (OA). In conclusion, this study demonstrates a correlation between body mass index and the incidence of osteoarthritis in patients at Ibnu Sina Hospital in Makassar.